Cognitive Biases and Investor Behavior: A Behavioral Finance Perspective on Stock Market Investment Decisions (International Journal of Environmental Sciences, 2025)
this study examines how personality traits, prospect theory elements, and heuristic factors affect stock market investment choices. By drawing on behavioral finance theories, the study highlights the critical role of individual traits, emotional inclinations, and cognitive biases in influencing investor behavior. Representativeness, herd behavior, overconfidence, anchoring, and availability heuristics are among the heuristic factors that have been examined. Along with personality variables, including self-esteem, emotional experience, optimism, and risk tolerance, prospect theory components like loss aversion, regret aversion, mental accounting, and cognitive dissonance were also investigated.The primary data was collected from individual investors with a sample size of 1200, 600 samples from Anantapur town and 600 samples from Bangalore city. The paper aims to understand cognitive biases in investment decisions in geographic areas.According to multivariate regression analysis, heuristic factors together explain 47% of the variance in investor behavior. Representativeness (β = 0.255) and overconfidence (β = 0.270) were the most significant predictors. Validation by statistics (R2 = 0.470, F(5,1194) = 211.92, p < 0.001) demonstrates how vital these biases are in influencing investment choices. The availability, anchoring, herd behavior, and overconfidence heuristics substantially impact behavior.The results highlight the importance of comprehending behavioral patterns to reduce cognitive biases and enhance investment methods. The study offers investors, legislators, and financial advisors’ important information by emphasizing the part played by emotional considerations and heuristic biases. It concludes that to handle the complexity of contemporary market dynamics; behavioral aspects must be incorporated into classic financial theories.